(untitled) (Ogigia. Revista Electrónica de Estudios Hispánicos, 2020)
The purpose of this work is to make a brief but complete journey troughout the inter-war’s humorous and erotic magazines, taking as a reference one of its main exponents: the magazine Muchas Gracias. The point of view of our approachment is considering that kind of texts as an absolutely valid and representative sign in order to analyze the new parameters of literary creation in the beginnings of the 20th Century.